2018
DOI: 10.14202/vetworld.2018.240-247
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementation of multistrain probiotic preparation in combination with vitamins and minerals to the basal diet on the growth performance, carcass traits, and physiological response of broilers

Abstract: Aim:The aim of the present study was to investigate the effect of supplementation of multistrain probiotic preparation in combination with vitamins and minerals to the broiler chicken diets on their growth performance, hematological parameters, and carcass traits.Materials and Methods:Two hundred and eighty-eight Lohmann 1-day-old broiler chicks were randomly allocated to four groups, i.e., control (without additional supplementation) and three experimental treatments where basal diet was enriched by 0.1%, 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
6
17
0
Order By: Relevance
“…It was apparent in the present study that dietary treatments did not produce any effect on carcass traits of the Indonesian indigenous crossbred chickens. Concomitant to our finding, treatment with either AGP [ 12 , 16 ], commercial B. subtilis [ 43 ] or multi-strain probiotic preparation in combination with vitamins and minerals [ 11 , 12 ] had no impact on the carcass traits of broiler chicks. Different from the above-mentioned studies, Shabani et al .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…It was apparent in the present study that dietary treatments did not produce any effect on carcass traits of the Indonesian indigenous crossbred chickens. Concomitant to our finding, treatment with either AGP [ 12 , 16 ], commercial B. subtilis [ 43 ] or multi-strain probiotic preparation in combination with vitamins and minerals [ 11 , 12 ] had no impact on the carcass traits of broiler chicks. Different from the above-mentioned studies, Shabani et al .…”
Section: Discussionsupporting
confidence: 56%
“…This inference was supported by the current findings showing a comparable effect of commercial B. subtilis and multi-strain probiotic preparation in combination with vitamins and minerals to most of parameters observed in the present study. Supplementation of certain minerals and vitamins into probiotic preparation was actually intended to compensate the possible damage of vitamins and minerals in the feed due to improper feed handling during transportation and storage [ 11 ]. Furthermore, supplementation was subjected to alleviate the detrimental effects of unfavorable conditions such as heat stress on poultry [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the data are consistent with previous experiments on broiler chickens given feed with the addition of a probiotic preparation in combination with vitamins and minerals (BC, B. licheniformis , and Bacillus megaterium ), where a lower WBC and number of eosinophils (p≤0.05) were found than for chickens without additives. As in our experiment, there were trends that dietary additives led to a lower (p=0.07) number of lymphocytes [ 35 ].…”
Section: Discussionsupporting
confidence: 53%
“…Sugiharto et al . (2018) reported that the lower level of serum uric acid in birds supplemented with 0.5% multistrain probiotics was associated with higher retention of protein in the body of birds [ 20 ]. The total numbers of Bacillus on days 30 and of LAB on days 20 and 30 detected in cloaca swabs from KKU213+CH403+SH8-fed broilers were significantly higher than those found in the swabs from the control group, which suggested that the probiotics altered the microbial gut population in a positive manner.…”
Section: Discussionmentioning
confidence: 99%